Rethinking the Iranian Islamic Revolution of 1979 with the Security Dilemma of the Cold War - BALCI, MERAL (My University, 2019)
The case of Iranian Revolution can be interpreted in different ways in the light of the fact that it isstill a revolution that continues to be written and discussed too much about. The study of the IranianRevolution in literature, in general, confronts a growing resistance with the influence of the oppositionpeople who oppose the oppression of the Pahlavi Dynasty dictatorship and grows under the influence ofthe Islamic phenomenon. However, in order to understand the Iranian Revolution, the perspective thatis focused on the internal dynamics will not be sufficient. The external dynamics and the interactionof external dynamics with these actors must be a further perspective that needs to be focused tounderstand this particular revolution.In this article, the differences of the Iranian Revolution are evaluated in a different perspective fromthe point of view of the literature. Rather than explaining the revolution with the historical process, itfocused on the external dynamics that constitute the historical process. While evaluating the externaldynamics, it is explained that the anarchy created by the Cold War in the international system throughthe security dilemma, and that the internal dynamic effect of this dilemma in a strategic country suchas Iran could be realized by developing the anti-imperialist identity building of Khomeini throughdiscourse and integrating all opposition groups. While evaluating the external dynamics, it is explainedthat the anarchy created by the Cold War in the international system through the security dilemma, andthat the internal dynamic effect of this dilemma in a strategic country such as Iran could be realizedby developing the Anti-Imperialist identity building of Khomeini through discourse and realizing theIslamic revolution of all opposition groups.

İran Devrimi bugün bile üzerine çok fazla yazılan, tartışılan bir devrim olması itibari ile farklı açılardan yorumlanabilmektedir. İran devriminin literatüre giren incelemeleri genel anlamda Pehlevi Hanedanlığının diktatörlüğünün baskısına karşı koyan muhalif halk ve İslam olgusunun etkisi ile büyüyen bir direniş olarak karşımıza çıkmaktadır. Ancak İran Devrimi’nin anlaşılması için sadece iç dinamiklere yoğunlaşılan bakış açısı yeterli olmayacaktır. Dış dinamikler ve dış dinamiklerin aktörler ile etkileşimi bu şahsına münhasır devrimi anlayabilmek için odaklanılması gereken ayrıca bir perspektif olmalıdır. Bu makalede, İran Devriminin farklılığı literatürdeki bakış açılarından farklı bir perspektif ile değerlendirilmiştir. Devrimi tarihsel süreç ile açıklamadan ziyade tarihsel süreci oluşturan dış dinamiklere odaklanılmıştır. Dış dinamikleri değerlendirirken Soğuk Savaşın uluslararası sistemde yarattığı anarşi, Güvenlik İkilemi üzerinden açıklanmıştır. Mevcut iki kutbun yarattığı ikilem ise İran gibi stratejik bir ülkede, Humeyni’nin ‘Anti-emperyalist’ kimlik inşasını oluşturarak tüm muhalif grupları birleştirebilmesine ve böylece de İslam Devrimini gerçekleştirebilmesine olanak sağlamıştır.
1979 İran İslam Devrimini ‘Soğuk Savaşın Güvenlik İkilemi’ ile Yeniden Düşünmek
Keywords: Uluslararası İlişkiler; Siyasi Bilimler